Boundary-value problems for charged hyperbolic-parabolic equations with characteristic line of changing type - Eleev, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We establish the unique solvability of some boundary-value problems for a mixed second-order hyperbolic-parabolic equation.